Association between dietary antioxidants, serum albumin/globulin ratio and quality of life in esophageal squamous cell carcinoma patients: a 7-year follow-up study - Zhang, Juwei; Zhou, Jinsong; Chen, Siting; Huang, Yue; Lin, Zheng; Deng, Yuan; Qiu, Minglian; Xiang, Zhisheng; Hu, Zhijian (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to explore the association between dietary antioxidant index (DAI) combined with serum albumin-to-globulin ratio (AGR) and postoperative Health-related quality of life (HRQOL) in patients with esophageal squamous cell carcinoma (ESCC).MethodsAll patients were newly diagnosed with ESCC and underwent radical esophagectomy. Dietary data and routine blood tests were collected preoperatively to compute DAI and AGR. HRQOL was assessed over 7 years post-surgery via telephone follow-up and analyzed longitudinally using a time to deterioration (TTD) model. The deterioration times were compared using the log-rank test, and the association of the combined DAI and AGR index with postoperative quality of life in ESCC patients was examined through Cox regression models.ResultsA total of 238 ESCC patients were included in the study. The results indicate that compared to the low DAI-AGR group, the high DAI-AGR group had a lower rate of deterioration events, and the time to deterioration in emotional functioning (p=0.014), dysphagia (p=0.042), and speech problems (p=0.023) were significantly delayed. Cox proportional hazard model revealed that preoperative high DAI-AGR was associated with improvement in emotional functioning (HR=0.575, 95% CI: 0.368-0.898) and speech problems (HR=0.525, 95% CI: 0.298-0.925) in ESCC patients postoperatively, which remained significant even after adjusting for covariates. The stratified analysis revealed that this improvement was associated with demographic and clinical characteristics.ConclusionsOur findings suggest that high preoperative DAI-AGR is linked to enhanced postoperative HRQOL in ESCC patients, offering crucial insights for patients, practitioners, and researchers.